Evaluation of the efficacy of visual acupotomy combined with rehabilitation training in the treatment of knee osteoarthritis - PAN Xigui; LIAN Xiaowen; FU Jiehui; ZHANG Zesheng; LIU Xuemei; XIU Zhongbiao (康复学报)
ObjectiveObserve the effect of ultrasound visualization needle combined with rehabilitation training for knee osteoarthritis .Methods70 patients with knee osteoarthritis, admitted from August 2021 to March 2023, were randomly divided into observation and control groups, with 35 patients each. 4 patients in the ultrasound knife group and 6 patients in the conventional treatment group withdrew.The observation group underwent treated under ultrasound guidance, combined with quadriceps rehabilitation training .ResultsThe efficacy of ultrasound visualization combined with rehabilitation training for knee osteoarthritis was compared between the two groups of patients, with no significant difference (P> 0.05).After treatment, VAS and WOMAC scores decreased in both groups, but the decrease was more obvious in the ultrasound knife group, with VAS score (P <0.05) and WOMAC score (P <0.01).Peak quadriceps torque value (PT) increased in both groups, but more significantly in the ultrasound knife group (P <0.01).The common lesions selected by tendon theory were 87.1% (27 / 31), 83.9% (26 / 31), 77.4% (24 / 31), and 74.2% (23 / 31), indicating echo enhancement, cyst fluid and synovial thickness. The selection of needle injection point and injection Angle and depth are shown in Table 5. The clinical effective rate of conventional therapy group was 86.2% (25 / 29), and 100% (31 / 31), statistically significant (P <0.01); 8 patients in conventional treatment group had minor adverse reactions, and only one patient in ultrasound knife group had minor adverse effects, and the clinical treatment safety was higher appraise.ConclusionUltrasound visualization of needle knife treatment combined with quadriceps rehabilitation training can accurately release the focus of the meridian tendons, stabilize the function of the knee joint, and improve the safety and effectiveness of the treatment, which is worthy of promotion .